Design entrepreneurship through fusion of art and design. - Wee, Daphne Huan Shian. (2009)
This graduate project seeks to showcase and create awareness of the abilities and artistic talents of persons with Down syndrome in Singapore to the public and community. With the aid of visual communications, it aims to market the artworks of persons with Down Syndrome. Believing that they should have equal opportunities to make a contribution to the society and which can provide and sustain as a source of income and independent living. The Visual Arts Exhibition “Filled With Glee” will showcase the artistic talents of persons with Down syndrome of Down Syndrome Association Singapore. It reflects their child-like characteristics and projects their positive, jovial and fun-loving attitudes. The artworks works as a medium of expression of their feelings and emotions to convey their aspirations to the community and share the joy, love and hope in life.